Exploration of Shared Gene Signatures and Molecular Mechanisms Between Periodontitis and Nonalcoholic Fatty Liver Disease - Xu, Wanqiu; Zhang, Zhengwei; Yao, Lihong; Xue, Bing; Xi, Hualei; Wang, Xiumei; Sun, Shibo (Frontiers in Genetics, 2022)
Background: Periodontitis is associated with periodontal tissue damage and tooth loss. Nonalcoholic fatty liver disease (NAFLD) has an intimate relationship with periodontitis. Nevertheless, interacted mechanisms between them have not been clear. This study was intended for exploration of shared gene signatures and latent therapeutic targets in periodontitis and NAFLD. Methods: Microarray datasets of periodontitis and NAFLD were catch from Gene Expression Omnibus (GEO) database. The Weighted Gene Co-Expression Network Analysis (WGCNA) was utilized for acquisition of modules bound up with NAFLD and periodontitis. We used ClueGO to carry out biological analysis on shared genes to search their latent effects in NAFLD and periodontitis. Another cohort composed of differential gene analysis verified the results. The common microRNAs (miRNAs) in NAFLD and periodontitis were acquired in the light of the Human microRNA Disease Database (HMDD). According to miRTarbase, miRDB and Targetscan databases, latent target genes of miRNAs were forecasted. Finally, the miRNAs–mRNAs network was designed. Results: Significant modules with periodontitis and NAFLD were obtained via WGCNA. GO enrichment analysis with GlueGo indicated that damaged migration of dendritic cells (DCs) might be a common pathophysiologic feature of NAFLD and periodontitis. The results of differential analysis in another cohort were highly accordant with the findings of WGCNA. We established a comorbidity model to explain underlying mechanism of NAFLD secondary to periodontitis. The analysis of miRNA pointed out that hsa-mir-125b-5p, hsa-mir-17-5p and hsa-mir-21-5p might provide potential therapeutic targets. Conclusion: Our study firstly established a comorbidity model to explain underlying mechanism of NAFLD secondary to periodontitis, found that damaged migration of DCs might be a common pathophysiologic feature of NAFLD and periodontitis, and provided potential therapeutic targets.